2017
DOI: 10.2139/ssrn.3069960
|View full text |Cite
|
Sign up to set email alerts
|

Labour Force Participation and Employment of Humanitarian Migrants: Evidence from the Building a New Life in Australia Longitudinal Data

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 80 publications
0
13
0
Order By: Relevance
“…For instance, a recent study of over 2000 refugees in Australia showed that pre‐immigration education is negatively correlated with employment outcomes (Cheng et al . 2019). Similarly, a study in the UK showed that refugees with managerial professions and higher‐educational backgrounds, such as postgraduate qualifications, took longer to find suitable employment, due to difficulties converting their qualifications, the paucity of bridging courses and the need for further local education experience (Shiferaw and Hagos 2002).…”
Section: Institutional‐level Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, a recent study of over 2000 refugees in Australia showed that pre‐immigration education is negatively correlated with employment outcomes (Cheng et al . 2019). Similarly, a study in the UK showed that refugees with managerial professions and higher‐educational backgrounds, such as postgraduate qualifications, took longer to find suitable employment, due to difficulties converting their qualifications, the paucity of bridging courses and the need for further local education experience (Shiferaw and Hagos 2002).…”
Section: Institutional‐level Factorsmentioning
confidence: 99%
“…An Australian study with similar findings suggests that wage discrepancies may be due to employers’ inability to understand, or lack of time and resources to recognize, home‐country qualifications (Cheng et al . 2019). Even so, a UK study found that, despite having local qualifications, refugees were still worse off in terms of their earnings when compared to other ethnic minority groups (Bloch 2008).…”
Section: Organizational‐level Factorsmentioning
confidence: 99%
“…Neither group of studies, however, focuses on the labour market outcomes of humanitarian migrants even though they are a significant sub-population of immigrants in Australia, whose pathway to settlement is vastly different from the one experienced by skilled migrants. Cheng et al (2019) used the first two BNLA survey waves to examine a series of human capital indicators, finding that humanitarian migrants' higher proficiency in spoken English is associated with an increased probability of their labour force participation. Using the first three waves of the BNLA survey data, Delaporte and Piracha (2018) found that English proficiency was associated with access to (stable) employment, the wage/earnings level and the educationoccupation mismatch.…”
Section: Existing Literaturementioning
confidence: 99%
“…Most existing studies on the labour market outcomes of humanitarian migrants in Australia focus on ethnically defined refugee groups or narrowly defined refugee groups, which exclude other humanitarian migrants. Two recent exceptions are Cheng et al (2019) and Delaporte and Piracha (2018), who examined the general relationships between human capital and labour market outcomes using representative panel data of humanitarian migrants in Australia. However, as we will elaborate shortly, these scholars did not examine the underlying mechanisms of these relationships.…”
Section: Introductionmentioning
confidence: 99%
“…A large body of literature has been published on the labour market outcomes of immigrants in advanced economies (e.g., Bettin, Patrizio, Francesco, Laura, & Ugo, 2019; Bettin, Turco, & Maggioni, 2014; Cheng et al, 2019, 2020; Chiquiar & Hanson, 2005; Islam & Parasnis, 2016; Kangasniemi, Mas, Robinson, & Serrano, 2012; Scheve & Matthew, 2001). Relatively fewer studies have focused on international migrant workers in developing countries, despite developing countries hosting more than one third of international migrants (OECD/ILO, 2018).…”
Section: Introductionmentioning
confidence: 99%